Diseño y especificación de los componentes principales y auxiliares - Darnond, Luis; Bertoni, Jorge A.; Fritzsche, Jürgen; Larumbe Valle, Juan M.; López, Raúl; Martínez, Gerónimo; Reatti, Ornar; Simchez, Simón (Comisión Nacional de Energía Atómica; Argentina, 1974)
Fil: Darnond, Luis Comisión Nacional de Energía Atómica; Argentina